KNOWLEDGE AUDIT FRAMEWORK : A CASE STUDY OF THE MALAYSIAN ELECTRICITY SUPPLY INDUSTRY (Journal of Information and Communication Technology, 2017)
Literature has concurred that knowledge audit promotes efficient management and exploitation of organizational knowledge. Due to the distinctive business environment of the electricity supply industry, the existing knowledge audit frameworks may not be suitable to be adopted â€˜as-they-areâ€™ by the industry. In this context, this research has proposed a knowledge audit framework that is specifically tailored to the environment of the electricity supply industry. Two main electricity companies in Malaysia were selected as the case companies for this research. The proposed knowledge audit framework aims to present a holistic way of assessing and analyzing the current knowledge environment of the electricity supply industry in Malaysia. The outcomes of the knowledge audit exercise could be used in developing a knowledge strategy that is aligned with the business strategies of the electricity companies.